2016
DOI: 10.3758/s13415-016-0490-8
|View full text |Cite
|
Sign up to set email alerts
|

Neuromodulation can reduce aggressive behavior elicited by violent video games

Abstract: Research has shown that exposure to violent media increases aggression. However, the neural underpinnings of violent-media-related aggression are poorly understood.Additionally, few experiments have tested hypotheses concerning how to reduce violent-media-related aggression. In this experiment, we focused on a brain area involved in the regulation of aggressive impulses-the right ventrolateral prefrontal cortex (rVLPFC). We tested the hypothesis that brain polarization through anodal transcranial direct curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 46 publications
3
64
1
Order By: Relevance
“…Both these games have been successfully used in previous studies (Gabbiadini et al, , ; Riva et al, ). In both the violent and the nonviolent video game conditions, participants first practiced by playing for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Both these games have been successfully used in previous studies (Gabbiadini et al, , ; Riva et al, ). In both the violent and the nonviolent video game conditions, participants first practiced by playing for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, priming effects should only play a role in very close temporal proximity to gameplay, and it is, therefore, difficult to observe the effects of VVGs on individuals’ aggressive behaviors over a longer period of time (e.g., >15 min). The repeated short‐term effects of VVGs could, therefore, elicit long‐term effects by developing aggressive knowledge structures (Allen et al, ; Anderson & Bushman, ; Calvert et al, ; Riva et al, ). These long‐term effects should occur over a long period of time due to the small effect size of VVGs.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the VLPFC is also implicated in emotional processing, and is located near the DLPFC [5]. Furthermore, research has shown that anodal tDCS over the VLPFC affects emotional processing and emotional reactivity [74][75][76][77]. Therefore, some caution is warranted for the specificity of the DLPFC stimulation in the current study.…”
Section: Discussionmentioning
confidence: 83%